Organic Nitrogen Fertilizer Selection Influences Water Use Efficiency in Drip-Irrigated Sweet Corn - Sukor, Arina; Qian, Yaling; Davis, Jessica G. (MDPI, 2023)
Organic farmers often rely on off-farm nitrogen (N) sources for mid-season N. Farmers can also produce cyano-fertilizer on-farm by growing N-fixing cyanobacteria (Anabaena spp.) in raceways and applying the cyanobacteria through irrigation systems. A two-year field study was conducted, and blood meal, feather meal, fish emulsion, and cyano-fertilizer were evaluated to determine whether the water use efficiency (WUE) of sweet corn (Zea mays) was affected by fertilizer type. Fish emulsion and cyano-fertilizer were supplied in four split applications through drip irrigation, while the blood meal and feather meal were subsurface banded pre-plant. Leaf gas exchange measurements were taken during tasseling. The amounts of phytohormone and Fe applied in organic N fertilizers were correlated with field water use efficiency (fWUE), instantaneous water use efficiency (iWUE), and leaf gas exchange components of sweet corn. A positive relationship was observed between the amount of salicylic acid (SA) applied with both iWUE (r = 0.71, p < 0.05) and fWUE (r = 0.68, p < 0.01). The amount of Fe applied was positively correlated with the leaf vapor pressure deficit (r = 0.54, p < 0.01) and transpiration rate (r = 0.53, p < 0.01). Cyano-fertilizer had the highest yield and WUE, likely due to the high amount of SA applied, although fish emulsion was comparable in year one. These relationships require further exploration to elucidate the mechanisms impacting WUE.